2009
DOI: 10.1007/s11282-009-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of intracoronal resorption in unerupted teeth in the permanent dentition: a retrospective study

Abstract: Objective To determine the prevalence, types of teeth, and distribution of intracoronal resorption in permanent dentition in a large population. Methods A total of 9,570 panoramic radiographs were screened, and 2,922 unerupted teeth were examined. Results The prevalence of intracoronal dentine defects was 1.55% in subjects and 0.95% in teeth. The highest prevalence of intracoronal radiolucencies was noted in the mandibular second molar (9.5%), followed by the maxillary second premolar tooth (4.7%). To our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
83
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(101 citation statements)
references
References 12 publications
10
83
3
5
Order By: Relevance
“…6 According to some studies, surgical intervention and restoration of an unerupted tooth or after eruption root canal treatment are recommended. [2][3][4][5][6] In the present case, the maxillary primary second molar tooth with PIR was extracted due to obstruction of the maxillary second premolar. The patient was then referred to an orthodontist for additional dental treatment.…”
Section: Casementioning
confidence: 99%
See 2 more Smart Citations
“…6 According to some studies, surgical intervention and restoration of an unerupted tooth or after eruption root canal treatment are recommended. [2][3][4][5][6] In the present case, the maxillary primary second molar tooth with PIR was extracted due to obstruction of the maxillary second premolar. The patient was then referred to an orthodontist for additional dental treatment.…”
Section: Casementioning
confidence: 99%
“…[1][2] However, some studies suggested that PIR was associated with local factors, such as chronic apical inflammation and ectopic eruption, or systemic factors. [3][4] A number of case reports described this defect in permanent teeth, using panoramic or bitewing radiographs. 1-6-8 As conventional radiographs Cone Beam Computed Tomographic Analysis of Pre-Eruptive Intracoronal Resorption in a Primary Tooth: A Very Rare Case A AB BS S T TR RA AC CT T Pre-eruptive intracoronal resorption (PIR) is very rare in primary teeth, and the etiology and factors associated with the resorptive process remain unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] No amelogenesis imperfecta, dentinogenesis imperfecta, hypophosphatemic rickets, or other dental or medical pathology that can affect the dental structure of teeth has been observed. 12 The aims of this report were to explain a case of PEIR, histopathologically analyze it, and provide awareness of this rare occurrence.…”
mentioning
confidence: 99%
“…[1][2][3]13,14 Süt dişinin periapikal inflamasyonun altında gelişmekte olan daimi dişi etkileyebileceği, ancak bu teorinin literatürdeki tüm olguları, özellikle üzerlerinde süt dişi yer almayan daimi molar diş-lerin defektlerini açıklamada yetersiz kaldığı bildirilmiştir. 1,2,[15][16][17] İntrakoronal radyolüsensiler radyografta çürük benzeri görüntü verse de, çürük teşhisi konulabilmesi için histolojik değerlendirmelerin dentinal tübüllerde bakteri varlığını göstermesi gerektiği, ancak pek çok olguda birincil amaç dişin ağızda tutulması olduğundan, histolojik delilin yetersiz olduğu, bazı araştırmacılar çalışmalarında çürük ve bakteri varlığı rapor etmekle birlikte, bunların parsiyel ya da tamamen ağız florasına açıl-dığı, gömülü sürmemiş bir dişte çürük görülebile-ceğini destekleyen ya da reddeden bir kanıtın bulunmadığı bildirilmiştir. 7,13,15,18 Rezorpsiyon pek çok sürmemiş dişte görülen intrakoronal radyolüsensinin etiyolojisiyle ilgili olarak rapor edilmiştir.…”
unclassified